Job Displacement, Relative Wage Changes, and Duration of Unemployment - Addison, John T.; Portugal, Pedro (Journal of Labor Economics, 1989)
Using special CPS data on displaced workers, this article investigates the wage consequences of job displacement in a framework that emphasizes the effects of past job duration(s) and unemployment duration(s) on postdisplacement wages. Our model also attempts to take account of the simultaneity between unemployment duration and the postdisplacement wage. It is found that duration strongly reduces subsequent earnings and that considerable overstatement of the loss in firm-specific training investments is implied by conventional routes to measuring wage losses.